Cambrian crude oil in ZS well field, Tazhong area: characteristics, genesis, and comparison with ordovician crude oil. (3rd May 2019) - Huo, Fei; Wang, Xingzhi; Xu, Zhiming; Huang, Huiwen; Qiang, Wei
Abstract: In this paper, the Cambrian crude oil and source-rock geochemistry in the ZS well field of Tazhong area, Tarim Basin, was analyzed using the gas chromatography-mass spectrometry (GC-MC). Moreover, the hydrocarbon source in the Tazhong was identified through oil–source correlation. The analysis of light hydrocarbons and biomarkers indicates that the Cambrian and Ordovician protokerogens are of marine sapropelic type formed in a strongly reducing environment. The result of oil–source correlation shows that both Cambrian crude oil in the ZS well field and Ordovician crude oil in the Tazhong area originated in the Cambrian–Lower Ordovician source rocks.